Operational Financial Management of Jami'atul Qura'wal Hufadz Islamic Boarding School Palembang - Siti Elly Sulastri; Tina Luvita Sari; Yuyun Marlina; Elza Rara Wijaya; Nur Hidayah (CV. Tripe Konsultan, 2022)
This study aims to see and analyze various issues related to operational financial management at the Jami'atul Qura'wal Hufadz Islamic Boarding School Palembang. This study uses the descriptive qualitative method. The type of research used is field research. Data collection methods used are observation, interviews and documentation. The subjects in this study were the administrators of the Jami'atul Qura'wal Hufadz Islamic Boarding School in Palembang. The results of this study are the implementation of the education financial system at the Jami'atul Qura'wal Hufadz Islamic Boarding School in Palembang administratively has shown positive financial management. Even tends to be systematic even though the bookkeeping management is still very simple because the bookkeeping system implements two-sided education financing. They are bookkeeping adjusted to government laws and regulations, which will later be changed to the source of funds for the government institution, and internal bookkeeping (sources of funds from parents of students or other parties that are not binding).